Editors’s Introduction to the Special Issue on "100 Years of Alan Turing and 20 Years of SLAIS" - Mladenić, Dunja; Muggleton, Stephen; Bratko, Ivan (Informatica)
Editors's Introduction to the Special Issue on "100 Years of Alan Turing and 20 Years of SLAIS"